Chemotherapy Associated Ovarian Failure - Mauri, Davide; Gazouli, Ioanna; Zarkavelis, Georgios; Papadaki, Alexandra; Mavroeidis, Leonidas; Gkoura, Stefania; Ntellas, Panagiotis; Amylidi, Anna-Lea; Tsali, Lampriani; Kampletsas, Eleftherios (Frontiers in Endocrinology, 2020)
As the incidence of malignancies in young adults is increasing, fertility preservation in cancer survivors arises as a major concern. Especially among female cancer patients, pregnancy rates are estimated to be 40% lower compared to women of the same age. Nowadays oncologists are to be preoccupied not only with their patients’ successful treatment, but also with the maintenance of the potential of the latter to conceive and obtain children. Chemotherapy associated ovarian failure (COF), refers to disruption of ovarian function both as an endocrine gland and as a reproductive organ, due to previous exposure to chemotherapy agents. Although the underlying mechanism is not fully understood, it is supposed that chemotherapy agents induce apoptosis of mature, functioning ovarian follicles, resulting in depression of estrogen levels and subsequent increase of FSH production by the hypophysis. Various chemotherapy agents have been associated with COF with the highest incidence being reported for patients undergoing combination regimens. Although a variety of alternatives in order to maintain ovarian function and fertility in female cancer survivors are available, adequately established practices to do so are lacking. Thus, it is of major importance to investigate further and collect sufficient evidence, aiming to guide patients and physicians in everyday clinical practice.